2016
DOI: 10.7861/clinmedicine.16-1-12
|View full text |Cite
|
Sign up to set email alerts
|

Practise what you preach: health behaviours and stress among non-consultant hospital doctors

Abstract: JournalClinical medicine (London, England) ABSTRACT IntroductionDoctors may experience better physical health than the general population, but higher rates of mental illness, suicide, depression, compassion fatigue and substance misuse are widely described. 1,2 In addition, workplace stress can lead to high rates of doctor burnout. 2Although the need to address doctors' health has been recognised, 2-5 medical training internationally gives little emphasis to self-care.2 In Ireland, some support services are a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 17 publications
2
14
0
1
Order By: Relevance
“…The overwhelming emphasis on issues of staffing, cover and leave in our study is in line with other studies and not surprising, given the current doctor shortage and growing patient population in Ireland 34 38. The shortage of doctors is a global phenomenon predicted to reach crisis levels by 2030 39–42.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The overwhelming emphasis on issues of staffing, cover and leave in our study is in line with other studies and not surprising, given the current doctor shortage and growing patient population in Ireland 34 38. The shortage of doctors is a global phenomenon predicted to reach crisis levels by 2030 39–42.…”
Section: Discussionsupporting
confidence: 90%
“…The preference of doctors in this study for primary-level, system-focused interventions over secondary-level, individual-focused training interventions is in line with preferences of doctors in Ireland uncovered in a recent study 34. It has also been shown that physicians expected to deal with their burnout individually feel less ‘resilient’ and take more personal ownership of their burnout than physicians who receive support from their hospital through system-level changes 35 36.…”
Section: Discussionsupporting
confidence: 83%
“…Our research shows that, in the field "Demand", the two groups have a similar overall score, falling into the red area. We may consider that this result is linked to the heavy workload and the kind of tasks often not suited to their abilities, which could be a cause of dissatisfaction and, sometimes, lead to interruption of the working activity (5,6,12,14,31,32). Even though this situation can lead to take targeted strategies, the workers of both groups achieve a score higher than the 80 th percentile in two of the eight items of this area, as it emerges in our results denoting they are not subject to intense and very fast work.…”
Section: Discussionmentioning
confidence: 99%
“…Finding time to attend a doctor’s appointment, the cost of lost work time, and lack of encouragement by employers have been postulated to cause barriers to doctors accessing appropriate healthcare, therefore leading to a higher likelihood of self-diagnosis and self-treatment 10. The convenience of self-prescription and a sense that doctors 'should' be able to manage their health problems have also been described 11. Physician health services, catering to the regular health needs of doctors, have been trialled in Norway to improve health outcomes for doctors 3…”
Section: Introductionmentioning
confidence: 99%